The Spillover of Socio-Moral Climate in Organizations Onto Employees’ Socially Responsible Purchase Intention: The Mediating Role of Perceived Social Impact - Schümann, Marlies; Stein, Maie; Tanner, Grit; Baur, Carolin; Bamberg, Eva (Frontiers in Psychology, 2021)
Due to the pressing environmental and social issues facing the global economic system, the role of organizations in promoting socially responsible behavior among employees warrants attention in research and practice. It has been suggested that the concept of socio-moral climate (SMC) might be particularly useful for understanding how participative organizational structures and processes shape employees’ prosocial behaviors. While SMC has been shown to be positively related to employees’ prosocial behaviors within the work context, little is known about the potential spillover effects of SMC (i.e., associations between SMC and employees’ prosocial behaviors outside the work context). The present study aims to address this gap by investigating how and why SMC is related to employees’ socially responsible purchase intention. Drawing on the relational job design framework, we argue that employees’ perceptions of their social impact may explain why SMC is positively related to responsible purchase intentions. We collected data from 492 employees working in various industries at two measurement points with a time lag of 12 months. Hypotheses were tested using path analysis, in which we controlled for the temporal stability of the study variables. The results showed that SMC was positively related to perceived social impact and socially responsible purchase intention and that perceived social impact was positively related to socially responsible purchase intention. In addition, we found a significant indirect relationship between SMC and socially responsible purchase intention through perceived social impact. The findings provide initial support for the spillover of employees’ work-related experiences onto their responsible purchase intentions within the nonwork domain. This study contributes to the literature by extending the traditional focus of SMC research on the development of moral reasoning skills to suggest that perceived social impact is an important mechanism underlying the relationship between SMC and prosocial behaviors. In terms of practical implications, this study suggests that organizational interventions designed to increase SMC may enhance employees’ perceptions of their social impact.